Designing an Expert System to Diagnose Myopic Eye Disease Using Mobile-Based Forward Chaining Method: Myopic Eye, Forward Chaining Method, Mobile Based - Hafiz Hafiz (Sean Institute, 2021)
Android adapted also in human civilization. The development of information technology affects many fields such as work, activities outside the home, vehicles and others. Eye health is a gift that cannot be paid for. Seeing how important eyes are to our lives, maintaining eye health is the main thing that we need to do every day. Maintaining eye health is very important because unfortunately our eyesight is lost. Many argue that in Southeast Asia many people suffer from eye diseases, especially myopia. Before something happens to the eye, we should take good care of it. A type of farsightedness when all types of myopia is actually an irregularity in focusing on the image of a visible object or a refractive error (ametropia). Using an expert system and applying a direct chain method designed to make it easier for patients to identify the type of myopic eye disease. And as knowledge for internet users about the importance of maintaining eye health in terms of myopia eye symptoms in the system.